LINGUISTIC MEANS OF ARGUMENTATION AND EVIDENCE PRESENTATION IN COURTROOM DISCOURSE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Courtroom discourse is a form of institutional communication that reflects the complex relationship between language and law. The process of reasoning and proving in court proceedings is carried out not only through legal norms, but also through linguistic and pragmatic means. This article analyzes the linguistic means used in the process of presenting evidence, constructing arguments, and proving them in court discourse. Within the framework of the study, speech acts, question constructions, evidential units, presuppositions, and pragmatic strategies are considered as important components of argumentation mechanisms in court proceedings. The results of the analysis show that language plays an important role in courtroom discourse not only as a means of transmitting information, but also as an instrument of persuasion and evidence.